PKM kotak pendingin kelompok penjual ikan keliling Kelurahan Bontoa - Edi Suhardi Rahman; Dyah Darma Andayani; Iwan Suhardi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Partners of the Community Partnership Program (PKM) are mobile fish seller groups selling fresh fish merchandise around Jeneponto Regency, South Sulawesi. The problems faced are: (1) aspects of fish quality, (2) marketing, and (3) lack of knowledge on how to maintain the quality of fish trade and what types of fish are needed by customers. The solutions offered by the service proposition team are (1) introducing cooler box technology for the place of their merchandise, (2) introducing information technology to improve marketing, and (3) transferring technology and training regarding cooler box technology and information technology to support marketing fish merchandise. The method of implementation carried out in this community service activity uses a participatory approach involving all members of the partner group. The approach taken is observation, lecture, question and answer, discussion, and training practices with a group of partners to provide solutions to problems. The results achieved by this activity are the traveling fish sellers partners who are equipped with understanding and skills that can be used independently in order to improve their welfare, even though this service activity has been completed. The expected target of output types are (1) scientific publications in journals /proceedings, (2) publications in mass media (print / electronic), (3) increase in turnover to partners, (4) increase in quantity and quality of products, and (5) improvement of community understanding and skills.